Autoimmune thyroid disease in Colombian patients with systemic lupus erythematosus (2015)
Objectives To determine the prevalence and the predictive factors of autoimmune hypothyroidism (AH) within a systemic lupus erythematosus (SLE) cohort and to analyse the current information concerning the prevalence and impact of autoimmune thyroid disease (AITD) and thyroid autoimmunity in patients with SLE. Methods A total of 376 patients with SLE were assessed for the presence of the following: (i) confirmed AH, (ii) positive thy-roperoxidase/thyroglobulin antibodies [TPOAb/TgAb] without hypothyroidism, (iii) nonautoimmune hypothyroidism and (iv) SLE patients with neither. Multivariate analysis and a classification and regression tree model were used to analyse data. The current information was discussed through a systematic literature review (SLR). Results In our cohort, the prevalence of confirmed AH was 12%. However, in euthyroid patients with SLE, TPOAb and TgAb were observed in 21% and 10%, respectively. Patients with confirmed AH were significantly older and had later age at onset of the disease. Smoking (adjusted odds ratio (AOR) 6·93, 95% CI 1·98-28·54, P = 0·004), Sjögren's Syndrome (SS) (AOR 23·2, 95% CI 1·89-359·53, P = 0·015) and positivity for anticyclic citrullinated peptide (anti-CCP) (AOR 10·35, 95% CI 1·04-121·26, P = 0·047) were associated with AH-SLE, regardless of gender and duration of the disease. Smoking and SS were confirmed as predictors of AH-SLE. In the SLR, the prevalence of AITD ranged from 1% to 60%. The factors associated with this polyautoimmunity were female gender, older age, smoking, certain autoantibodies, SS, and cutaneous and articular involvement. Conclusions AITD is frequent in SLE and does not affect the severity of SLE. Identified risk factors will assist clinicians in the search for AITD. Our results encourage smoke-free policies in patients with SLE. © 2014 John Wiley and Sons Ltd.